2022
DOI: 10.1186/s40634-022-00449-z
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and radiological effectiveness of autologous bone marrow derived osteoblasts (ABMDO) in the management of avascular necrosis of femoral head (ANFH) in sickle cell disease (SCD)

Abstract: Purpose Avascular necrosis of the femoral head is a common issue faced by orthopaedic surgeons that ranges between 10 and 18%, but in patients with SCD, the incidence reaches 30%. There is no definite treatment except joint arthroplasty. Regenerative medicine is an option to cure or delay joint arthroplasty. We report here our experience with the injection of ABMDO to manage ANFH and report our medium-term results, the progression of the ANFH if any and the delay in total hip arthroplasty. (THA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Our results agreed with Sadat-Ali et al, who showed significant improvement both in VAS and mHHS at serial follow-ups in SCD patients treated with AALCO [ 15 ].The main limitations of this study include its small size and short duration of follow-up. Further large-scale prospective studies with comparative groups involving core decompression alone or conservative management with long-term follow-ups may offer better insights into the efficacy of this treatment modality.…”
Section: Discussionsupporting
confidence: 92%
“…Our results agreed with Sadat-Ali et al, who showed significant improvement both in VAS and mHHS at serial follow-ups in SCD patients treated with AALCO [ 15 ].The main limitations of this study include its small size and short duration of follow-up. Further large-scale prospective studies with comparative groups involving core decompression alone or conservative management with long-term follow-ups may offer better insights into the efficacy of this treatment modality.…”
Section: Discussionsupporting
confidence: 92%